Optimalisasi Pengelolaan Rak Recekan di Subdepartemen Groceries PT. XYZ Menggunakan Metode DMAIC - Ashiddiqie, Mohamad Reza; Akbardin, Juang; Wulansari, Dwi Novi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines display inconsistencies in bulk shelving at the Groceries Subdepartment of PT XYZ, a multinational retail company in Cibubur, West Java. Using a qualitative descriptive approach with the DMAIC method (Define, Measure, Analyze, Improve, Control), the research identified that 46% of products on bulk shelves experienced placement errors, including out-of-shelf products (18%), non-compliance with FEFO principles (16%), and defective products (11%). Root cause analysis using fishbone diagrams revealed issues in four aspects: human (insufficient staff training), method (lack of SOPs), process (inadequate labeling systems), and environment (inefficient shelf layout). Improvement implementations included regular training programs, SOP development, clear labeling systems, and shelf layout redesign. Results showed significant Improvements in operational efficiency and reduction in product arrangement errors, along with the establishment of a sustainable Control system to prevent similar problems in the future.